RECOMBINANT MATRIX PROTEIN OF THE RABIES VIRUS - Mukantayev , K.; Shustov , A.; Tursunov , K.; Ingirbay , B.; Adish , Zh.; Ramanculov , E.; Mukanov , K. (Eurasian Journal of Applied Biotechnology, 2016)
Matrix proteins of RNA viruses are the main structural components and are required for virus assembly. The assembly of these virus particles is based on the ability of binding of the matrix protein to the nucleocapsid. This property suggests a promising role for the matrix protein, as it acts as a bridge between the nucleocapsid and plasma membrane. Analysis of literature on the biological functions of basic components of the rabies virus andthe spread of rabies in the Republic of Kazakhstan showed the importance of research on the recombinant matrix antigen of the virus. In this study, we used genetic engineering to show the results of receipt ofthe recombinant matrix protein of the rabies virus. As a result of research carried out design of the expression genetic construction containing gene of matrix protein of the rabies virus, and was performed synthesis of this gene with length 654 nucleotides under de novo conditions. The nucleotide sequence of the synthesized gene showed the correct assembly. Using expression plasmids, anEscherichia coli strain that produced the recombinant matrix antigen of the rabies virus was obtained. Electrophoretic analysis showed the expression of the protein with a molecular weight of 41 kDa. We developed protocols for the cultivation of the obtained strain and purification of the recombinant matrix antigen. Immunization of mice and analysis of sera from the immunized mice with the enzyme-linked immunosorbent assay were used to study the immunogenic properties of the recombinant antigen.